Intranasal Administration of Cold-Adapted Live-Attenuated Eurasian Avian-like H1N1 Vaccine Candidate Confers Protection Against Different-Lineage H1N1 Viruses in Mice - Qiu Zhong; Zuchen Song; Fei Meng; Yanwen Wang; Yijie Zhang; Zijian Feng; Yali Zhang; Yujia Zhai; Yan Chen; Chuanling Qiao; Hualan Chen; Huanliang Yang (Vaccines)
Background/Objectives: Eurasian avian-like (EA) H1N1 swine influenza viruses, with their persistent evolution and zoonotic potential, seriously threaten both swine and human health. The objective was to develop an effective vaccine against these viruses. Methods: A cold-adapted, temperature-sensitive live-attenuated influenza vaccine (LAIV) candidate, GX18ca, was developed. It was derived from the wild-type EA H1N1 strain A/swine/Guangxi/18/2011 (GX18) through serial passaging in embryonated eggs at temperatures decreasing from 33 °C to 25 °C. Its characteristics were studied in mice, including attenuation, immune responses (mucosal IgA, serum IgG, IFN-γ+ CD4+/CD8+ T-cell responses), and protective efficacy against homologous (GX18), heterologous EA H1N1 (LN972), and human 2009/H1N1 (SC1) viruses. Results: GX18ca showed cold-adapted and temperature-sensitive phenotypes. In mice, it was attenuated, with viral titers in the nasal turbinates and lungs reduced 1000–10,000-fold compared to the wild-type strain, and it cleared by day 5 post infection. Intranasal immunization elicited strong cross-reactive immune responses. Mucosal IgA had broad reactivity, and serum IgG titers reached high levels. IFN-γ+ CD4+/CD8+ T-cell responses were detected against all the tested viruses. A single dose of GX18ca fully protected against GX18 and LN972 challenges, and two doses significantly reduced SC1 lung viral loads, preventing mortality and weight loss. Conclusions: GX18ca is a promising LAIV candidate. It can induce broad immunity, addressing the cross-protection gaps against evolving EA H1N1 SIVs and zoonotic H1N1 variants, which is crucial for swine influenza control and pandemic preparedness.